Cardiovascular Effects of Antiretroviral Drugs: Clinical Review - Filardi, Pasquale P.; Paolillo, Stefania; Marciano, Caterina; Iorio, Annamaria; Losco, Teresa; Marsico, Fabio; Scala, Oriana; Ruggiero, Donatella; Ferraro, Sergio; Chiariello, Massimo (Cardiovascular & Haematological Disorders - Drug Targets, 2008)
In HIV infected patients an increased occurence of cardiac events has been demontrated from the introduction of highly active antiretroviral therapy (HAART). Antiretroviral drugs' regimens are, in fact, associated with several metabolic side effects, such as dyslipidemia, impaired glucose metabolism and abnormal body fat distribution, that increase the cardiovascular risk of HIV subjects. In addition, HIV infection itself, the chronic inflammatory status and the relevant presence in this population of some of the traditional cardiovascular risk factors contribute to an higher incidence of cardio and cerebrovascular events. In last years several studies showed the occurence of carotid vascular impairment in patients in treatment with protease inhibitors (PI). Similarly the DAD Study reported an increase of 26% of the risk of myocardial infarction in patients on HAART and that this risk is indipendently associated with longer exposure to PI, even after multivariate adjustments. A correct evaluation of the metabolic status before starting HAART and an adeguate control of the drugs-related metabolic abnormalities may reduce the incidence of cardiac events and still improve HIV patients prognosis. This review will focus on the metbolic effects of antiretroviral drugs and to the contribution of combination antiretroviral therapy on cardiovascular risk.
Keywords: myocardial infarction